Pengaruh Kadar Air Gabah Terhadap Kinerja Penggilingan Padi - Siti Asfiatul Mukaromah; Agus Haryanto; Siti Suharyatun; Tamrin Tamrin (Jurnal Agricultural Biosystem Engineering, 2022)
The moisture content of raw rice grains is an important factor that determines the quality of rice produced from milling. This study aimed to determine the effect of rice grain moisture content on rice milling performance which includes yield, degree of whiteness of rice, and proportion of head rice, broken rice, and groat rice. This research consisted of two stages, namely collecting data and samples at the rice mill and testing the quality of white rice. This study used 50 samples of raw rice grain and white rice produced from rice mills in Pring Sewu. The results showed that RMU worked well and produced a rice yield of 63.12%. The results also concluded that raw grain moisture content does not affect the quality of rice. White rice produced from milling had a whiteness index of 63.87 with the proportion of head rice of 73.59%, broken rice of 14.91%, and rice bran of 4.87%.